Efektivitas Layanan Pendampingan Administrasi Pindah Penduduk Di Kantor Kelurahan Karang Pilang Kota Surabaya - Risda Wulan Nur Octafiani; Sri Wibawani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Population administration control is to arrange and control population documents and data, one of which is registration of population transfers. Registration of population movements is very important for population administration because it provides an accurate and up-to-date data base, which can be used as a reference in planning development and public services in the future. The purpose of this study was to determine the effectiveness of administrative assistance services for moving residents in the city of Surabaya, especially the Karang Pilang Village, which includes human resources, population data, infrastructure in the Karang Pilang Village. The research method used is qualitative with a descriptive approach. The informants in this study were employees of the Karang Pilang Village office, local residents, RT RW administrators, and KSH (Surabaya Hebat Cadre). Data collection techniques through interviews, observation, and documentation which are then carried out by condensing data, presenting data, and drawing conclusions. The results of the study show that the effectiveness of administrative assistance services for moving residents in Karang Pilang Village, Surabaya City has been implemented quite effectively. It's just that, there are still obstacles such as a lack of human resources that need to be added so that the service process can be accelerated more easily.